Omicron XBB.1.5 subvariant causes severe pulmonary disease in K18-hACE-2 mice - Elsharkawy, Amany; Stone, Shannon; Guglani, Anchala; Patterson, Lila D.; Ge, Chunyu; Dim, Chinonye; Miano, Joseph M.; Kumar, Mukesh (Frontiers in Microbiology, 2024)
Owing to their continuous evolution, severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) variants of concern (VOCs) display disparate pathogenicity in mouse models. Omicron and its sublineages have been dominant worldwide. Compared to pre-Omicron VOCs, early Omicron subvariants reportedly cause attenuated disease in human ACE-2-expressing mice (K18-hACE-2). In late 2022, the frequency of Omicron subvariant XBB.1.5 rapidly increased and it progressively replaced other circulating strains. The emergence of new strains requires current SARS-CoV-2 clinical animal model re-evaluation. In this study, we aim to characterize XBB.1.5 pathogenesis in K18-hACE-2. Herein, we demonstrated that XBB.1.5 infection is associated with significant weight loss, severe lung pathology, and substantial mortality. Intranasal XBB.1.5 infection resulted in 100% mortality in K18-hACE2 mice. High virus titers were detected in the lungs on days 3 and 5 after infection. Moreover, XBB.1.5 productively infected the cells within the nasal turbinate, olfactory bulb, intestines, and kidneys. In addition, in a subset of infected mice, we detected high virus titers in the brain. Consistently, we detected high viral antigen expression in the lungs. Furthermore, we observed severe lung injury hallmarks (e.g., immune cell infiltration, perivascular cuffing, and alveolar consolidation). Using immunofluorescence labeling and cytometric analysis, we revealed that XBB.1.5 infection leads to CD45+ cell influx into the lung parenchyma. We further demonstrated that most immune infiltrates are CD11b+ CD11c+ dendritic cells. Additionally, we detected significant induction of proinflammatory cytokines and chemokines in infected lungs. Taken together, our data show that Omicron subvariant XBB.1.5 is highly pathogenic in K18-hACE2 mice.